Constructing Model of Integrated Zakat and Waqf Empowerment for Achieving Food Security and Poverty Alleviation - Rahmadhani, Putri; Rohim, Ade Nur (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2024)
Food security is one of the crucial factors in poverty alleviation, where adequate access to food can improve societal welfare and economic capacity. In Islam, zakat and waqf are essential instruments with great potential to support food security and poverty alleviation. This study aims to design a model that integrates zakat and waqf into an economic empowerment program based on food security to alleviate poverty. The proposed model, Zakat and Waqf Integration for Food Security Empowerment focuses on utilizing consumptive zakat funds for urgent food needs, followed by productive zakat for initial agricultural needs such as seeds and fertilizers, and the use of waqf funds, in the form of money and assets, to support long-term agricultural financing. The study results indicate that the integration of zakat and waqf within a single model has significant potential, given the growing potential of zakat and waqf in Indonesia, coupled with Government support for food self-sufficiency, making this model relevant. This model is expected to be an innovative solution in strengthening food security as an effort to alleviate poverty.